2017
DOI: 10.1007/s40145-017-0227-3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Weibull parameters from the mean value and the coefficient of variation of the measured strength for brittle ceramics

Abstract: Accurate estimation of Weibull parameters is an important issue for the characterization of the strength variability of brittle ceramics with Weibull statistics. In this paper, a simple method was established for the determination of the Weibull parameters, Weibull modulus m and scale parameter 0  , based on Monte Carlo simulation. It was shown that an unbiased estimation for Weibull modulus can be yielded directly from the coefficient of variation of the considered strength sample. Furthermore, using the yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Empirical PDFs of: a) normalized c v and b) normalized m eslus, m tr , which is consistent with the previous studies[19,20,25]. On the other hand, although a slight increasing tendency with increasing m tr was observed for the coefficient of variation c v , all the curves shown inFig.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Empirical PDFs of: a) normalized c v and b) normalized m eslus, m tr , which is consistent with the previous studies[19,20,25]. On the other hand, although a slight increasing tendency with increasing m tr was observed for the coefficient of variation c v , all the curves shown inFig.…”
supporting
confidence: 90%
“…As a supplement to the previous studies, the present study will report a comprehensive comparison of the applicabilities between Weibull distribution and normal distribution based on Monte-Carlo simulations, with a special emphasis on the accuracy of the prediction of the stress level corresponding to a given fracture probability. Previous studies based on Monte-Carlo simulations [21,25] have confirmed that, for a given strength sample, the estimated values of Weibull parameters m and σ 0 can be determined directly and accurately with the average value and the standard deviation of the sample, implying that a sample of strength data following a Weibull distribution may also be well described with a normal distribution and vice versa. This is the main reason why we select both Weibull distribution and normal distribution as the study subjects.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In 1989, van der Zweig [28] presented the same Robinson relation, but without citing prior works [11,16,26]. Three more approximate expressions have been published by [29][30][31] as follows (in the order of appearance):…”
Section: Approximate Methods Of Weibull Modulus Estimationmentioning
confidence: 99%
“…This phenomenon is caused by various flaws types, flaw positions and extension rates of flaws [1][2] . Naturally, strength of brittle materials is typically characterized by using statistical distribution functions (Weibull statistics) [3][4] .…”
mentioning
confidence: 99%